2010
DOI: 10.1152/ajpgi.00127.2010
|View full text |Cite
|
Sign up to set email alerts
|

Accurate localization of a fall in pH within the ileocecal region: validation using a dual-scintigraphic technique

Abstract: SM. Accurate localization of a fall in pH within the ileocecal region: validation using a dual-scintigraphic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 44 publications
2
73
0
Order By: Relevance
“…It is known that up to 15% of subjects fail to show a characteristic sharp fall in pH at the ICJ. 11 Zarate et al 11 wondered if this is related to ileocolic valve competence. Roland et al 6 found an association between a low pressure prior to the ICJ and small intestinal bacterial overgrowth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that up to 15% of subjects fail to show a characteristic sharp fall in pH at the ICJ. 11 Zarate et al 11 wondered if this is related to ileocolic valve competence. Roland et al 6 found an association between a low pressure prior to the ICJ and small intestinal bacterial overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…After the GE, a steady rise in the pH followed by a plateau represents the passage through the small bowel. A drop of 0.5-2.0 pH units usually occurs when the capsule enters the colon (due to bacterial fermentation), 11 thereby defining the ICJ. After the ICJ an erratic pH profile in the colon is characteristic.…”
Section: Physician-confirmed Ileocolic Junctionmentioning
confidence: 99%
“…In an elegant study using radioisotopes, the pH change was validated with cecal arrival time. 8 This pH drop in the ileocecal region is a result of fermentation in cecum and short-chain fatty acids production which is maximal in this region. 9 It is possible that in 15% of subjects, this pH drop is not observed and this may be related to the ileocecal valve incompetence.…”
Section: Normal Landmarksmentioning
confidence: 99%
“…9 It is possible that in 15% of subjects, this pH drop is not observed and this may be related to the ileocecal valve incompetence. 8 Body exit time is denoted by a temperature drop to room temperature and/or loss of signal with bowel movement.…”
Section: Normal Landmarksmentioning
confidence: 99%
“…Changes in pH are signifi cant, ranging from pH 1 to 2 in the fasted stomach, through to pH 7 to 8 in the distal regions of the GI tract. Characteristic changes in pH are observed, including a reduction in pH, generally of at least 1 pH unit [ 16 ], in the caecum as a result of microbial activity. However, in the small intestine, inter-subject variability is low, with variation (CV%) typically less than 10 % [ 17 , 18 ] (Fig.…”
Section: Regional Variationsmentioning
confidence: 99%